The effect of creep and other time related factors on plastics and elastomers - McKeen, Laurence W. (William Andrew, 2015)
This reference guide brings together a wide range of critical data on the effect of creep and other long term effects on plastics and elastomers, enabling engineers to make optimal material choices and design decisions. The data are supported by explanations of how to make use of the data in real world engineering contexts and provides the long-term properties data that designers need to create a product that will stand the test of time. This new edition represents a full update of the data, removing all obsolete data, adding new data, and updating the list of plastics manufacturers. Addition.
Keywords: Plastics -- Thermal properties.; Plastics -- Testing.; Elastomers -- Thermal properties.; Elastomers -- Testing.; elektronické knihy; electronic books